Fires in Indonesia: causes, costs and policy implications - Center for International Forestry Research (Center for International Forestry Research, 2002)
This infobrief provides key points that when fire is used to clear forest allocated to other land uses, such as plantations, fire is not the underlying cause of forest loss. In this case, the land allocation process needs to be addressed to reduce deforestation. • There is no single 'fire problem'. Rather, there are a range of fire-related problems that require their own appropriate policy response, such as smokehaze pollution, forest degradation and deforestation. Large-scale land clearing for plantations and small-scale livelihood activities are both major causes of the peat-land fires that produce most of Indonesia's smoke haze pollution and carbon emissions. Legislation governing fire use should be revised so that it a) bans those fires that cause significant smoke haze effects, such as peat-land fires, and b) regulates fire-uses that cause unwanted local effects resulting from smoke. Consideration should be given to including peat lands in the second commitment period of the Kyoto Protocol. As the severity and impacts of fires increases worldwide, there needs to be more focus on analyzing the policy and economic factors of fires.